Perilaku makan berlebih dan hubungannya dengan kegemukan pada anak prasekolah - Herni Dwi Herawati; Indria Laksmi Gamayanti; A. Fahmy Arif Tsani; I Made Alit Gunawan (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2016)
Backgrounds: Obese children is a serious health problem. Obesity in childhood if it’s not handled properly will cause obesity up to adolescence and adulthood. Eating behavior in children plays an important role on the prevalence of obesity.Objectives: This study aims to determine the correlation of excessive eating behavior (overeating, enjoyment of food, desire to drink) with overweight in preschool children.Methods: The study used case control design adjusted for age and sex. The research subjects were taken randomly from 53 early childhood schools in the city of Yogyakarta. Subjects were mothers who has preschool children aged 3-5 years. The subjects were divided into 2 groups: cases who have Z score> 2 SD (n = 101) and control have Z score -2 up to 2 SD (n = 101) were adjusted for age and gender. Behaviors of food approach were assessed using CEBQ (Children Eating Behavior Questionnaire). The nutritional status of parents was determined by using BMI (Body Mass Index). Data of birth weight and socioeconomic was obtained by interviews directly to the mother. Data were Analyzed  by Mc Nemar and Conditional Logistic Regression.Results: There was correlation enjoyment of food with overweight (p < 0.05, OR 4.33, 95% CI: 1.74-12.87). There was no correlation overeating (emotional overeating / food responsiveness) with overweight (p > 0.05, OR 0, 95% CI : 0.02 to 0.00). There was no correlation desire to drink with overweight (p > 0.05, OR 1.5, 95% CI 0.47 to 5.12). Enjoyment of food behavior is accompanied by nutritional status of obese mothers had significant association with overweight (p < 0.05, OR:3.71, 95% CI: 1.12 to 4.05).Conclusions: Enjoyment of food behavior was risk factor of overweight in preschool children. Educator in early childhood schools hopefully can give information to parents about prevention and intervention of obesity in preschool children, which associated with food  approach and obesity. Future research needs longitudinal studies to better know the causal behavior of food approach to obesity in preschool children. KEYWORDS: excessive eating behavior, overweight, preschool children